Question -13

Algebra Level 4

If x = c y + b z x=cy+bz , y = a z + c x y=az+cx and z = b x + a y z=bx+ay , where x , y , z 0 x,y,z \ne 0 , then find the value of ( a 2 + b 2 + c 2 ) (a^2+b^2+c^2) .


Looking for Top Rank in JEE ? Alright, then go for this set : Expected JEE-Mains-2015-B .
1 a b c 1-abc 1 + a b c 1+abc 1 2 a b c 1-2abc 1 + 2 a b c 1+2abc

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Karan Siwach
Mar 2, 2015

jee mains style :p

let x = y = z = 1 x=y=z=1

this will give us a + b = b + c = c + a = 1 a+b=b+c=c+a=1

and thus a = b = c = 1 / 2 a=b=c=1/2

and now just checkout for the right option !

i did the same.....don't know why this question is level 4??? (As of now)

Kislay Raj - 6 years, 3 months ago

@Sandeep Bhardwaj Sir i cant publish a solution as i pressed wrong option :P .

For exact and short solution we can use cramer's rule . For having non trivial solution Delta = 0 . solving this we get a^2+b^2+c^2 = 1-2abc

Prakhar Bindal - 4 years, 3 months ago

someone pls provide legitimate solution. i tried multiplying equations to get ax + by + cz on LHS, and equated the modulus of the 2 sides of equation, but did not get answer in format.

Saket Joshi - 6 years, 3 months ago
Anubhav Bhatia
Mar 7, 2015

We have x=cy+bz now put value of y in this equation
we will get (1-c^2)X=(ac+b)Z .......1 Now put value of y in third equation
We will have (ac+b)X=(1-a^2)Z.........2 Divide 1. By 2 We will reach to req.d answer

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...